2018
DOI: 10.1038/s41593-018-0265-3
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cell-type-specific transcriptomes by microRNA networks during human brain development

Abstract: MicroRNAs (miRNAs) regulate many cellular events during brain development by interacting with hundreds of mRNA transcripts. However, miRNAs operate non-uniformly upon the transcriptional profile with an as yet unknown logic. Shortcomings in defining miRNA-mRNA networks are limited knowledge of in vivo miRNA targets, and their abundance in single cells. By combining multiple complementary approaches, AGO2-HITS-CLIP, single-cell profiling, and innovative computational analyses using bipart… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
128
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(132 citation statements)
references
References 73 publications
3
128
0
1
Order By: Relevance
“…MicroRNAs (miRNAs) are small, endogenous, noncoding RNAs that negatively regulate gene expression at the post‐transcriptional level by binding to the “seed region” located in the 3’‐untranslated region (3’‐UTR) of their target mRNA (Mahmoudi & Cairns, ). MiRNAs are considered as a group of regulators in various biological processes, such as cell proliferation, differentiation, apoptosis, and cycle regulation (Bhaskaran et al, ; Mansini et al, ; Nowakowski et al, ). Changes in miRNA expression may cause cellular malfunction and result in disease phenotypes, including AD and cancers (Nagaraj et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MicroRNAs (miRNAs) are small, endogenous, noncoding RNAs that negatively regulate gene expression at the post‐transcriptional level by binding to the “seed region” located in the 3’‐untranslated region (3’‐UTR) of their target mRNA (Mahmoudi & Cairns, ). MiRNAs are considered as a group of regulators in various biological processes, such as cell proliferation, differentiation, apoptosis, and cycle regulation (Bhaskaran et al, ; Mansini et al, ; Nowakowski et al, ). Changes in miRNA expression may cause cellular malfunction and result in disease phenotypes, including AD and cancers (Nagaraj et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs are considered as a group of regulators in various biological processes, such as cell proliferation, differentiation, apoptosis, and cycle regulation (Bhaskaran et al, 2019;Mansini et al, 2018;Nowakowski et al, 2018). Changes in miRNA expression may cause cellular malfunction and result in disease phenotypes, including AD and cancers (Nagaraj et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in tissue harvesting and sequencing technologies have allowed detailed analyses of genome‐scale gene expression profiles at the level of single‐cell populations in the context of brain and behavior studies (Chalancon et al, ; Lacar et al, ; Mo et al, ; Moffitt et al, ; Nowakowski et al, ; Raj et al, ). These approaches have led to systems‐level insights into the molecular substrates of neural function and to the discovery and validation of candidate pathways regulating physiology and behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in tissue harvesting and sequencing technologies have allowed detailed analyses of genome-scale gene expression profiles at the level of single-cell populations in the context of brain and behavior studies (Chalancon et al, 2012;Lacar et al, 2016;Mo et al, 2015;Moffitt et al, 2018;Nowakowski et al, 2018;Raj et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Within large-brained species, differences also exist between cortical regions (Lukaszewicz et al, 2005), and particularly between prospective folds and fissures (Reillo et al, 2011). Primate-and human-specific genes have been identified that promote cortical progenitor cell amplification and neurogenesis, including protein-coding genes (Fiddes et al, 2018;Florio et al, 2018;Suzuki et al, 2018), and microRNAs that target cell cycle proteins (Arcila et al, 2014;Nowakowski et al, 2018). Whereas these genes may contribute to the emergence of primate-specific features (Florio et al, 2017;Nowakowski et al, 2018), they do not explain differences across phylogeny between mammals with big and small brains (i.e., human, ferret versus mouse).…”
Section: Introductionmentioning
confidence: 99%